AN EXPLORATION OF PERCEIVED BARRIERS TO HEALTH SERVICES AMONGST OLDER PEOPLE IN BONGO DISTRICT - Adongo, Vincent Agambila; Davis, Dr. Samantha (Global Journal of Health Sciences, 2020)
Purpose: The research was done to explore perceived barriers to health care services amongst older people in Bongo. Methodology: Using a qualitative methodology, a case study design was employed in the study. A qualitative approach was chosen because of the need to understand the phenomena of healthcare access from a personal perspective. The study was conducted in Bongo District in the Upper East Region of Ghana. Bongo District has six sub-districts with one hundred and forty three (143) communities and a population of 84,545. People aged 60 and above constitute 9.7% of the population. The District has one District Hospital that serves as a referral center for the sub-districts and neighboring communities from Burkina Faso. Central sub-district was randomly selected for the study using folded pieces of paper. A purposive sampling strategy was used and ten elderly people (aged 60 years or above) were recruited by door-to-door. Individual interviews were conducted using an interview guide. Interview material was transcribed verbatim and coded to be presented as results. Findings: The findings identified poverty, health insurance, long waiting times at hospital, traditional beliefs, health workers attitude, transportation, and lack of drugs at the health facilities as major barriers to health care access. Respondents prefer the hospital as their first choice of contact when sick but do not necessarily patronize the health facilities partly due to traditional beliefs, trust in herbalists, and poverty. Unique Contribution to Theory, Practice and Policy: From the findings, the researcher recommended that future human resource plan should include training of geriatric nurses and doctors to help address the specific needs of the aged. The health system should strengthen monitoring on quality assurance and quality controls to reduce waiting times and meet minimum pharmacy stock levels. Social support structures especially for the elderly at the community level should be promoted.